Emerging Issues and Controversies in Infectious Disease - Fong, I.W. (Springer, 2017)
This new volume of the "Emerging Infectious Diseases of the 21st Century" series is an up to date, state-of-the-art review on several important infections challenging clinicians, from the general practitioner to the various subspecialists that deals with infections.